The intersection of climate technology and public diplomacy: Insights into policy and implementation - Jaeryoung Song (Sustainable Futures)
Climate change represents one of the most critical challenges to global ecosystems, human survival, and sustainable development. Addressing these issues requires not only technological innovation but also strategic public diplomacy to enhance international collaboration and stakeholder engagement. This study investigates the potential of climate technology-driven public diplomacy as a means to bridge the gaps between developed and developing nations, promote equitable technology dissemination, and contribute to global climate action. Using a qualitative methodology, including focus group interviews and surveys conducted over four years with 21 experts from industry, public R&D, government, and civil society, this research provides a comprehensive analysis of stakeholder perceptions and effective communication strategies. The findings reveal that public diplomacy can serve as a catalyst for adopting and disseminating climate technologies, particularly in developing nations with limited access to such innovations. Stakeholder-specific differences were evident, highlighting the need for tailored diplomatic approaches to maximize impact. The study identifies Korea's unique position, owing to its development trajectory, as a leader capable of connecting advanced and emerging economies. Key outcomes include a multi-stakeholder collaboration framework, recommendations for strategic communication campaigns, and tailored diplomatic strategies to promote equitable adoption of climate technologies. By aligning technological innovation with diplomatic efforts, this research offers actionable insights for policymakers and practitioners to advance global climate resilience and achieve sustainability goals through inclusive and strategic partnerships.